Functional analysis and in vitro correction of splicing FAH mutations causing tyrosinemia type I. (21st August 2013) - Pérez‐Carro, R.; Sánchez‐Alcudia, R.; Pérez, B.; Navarrete, R.; Pérez‐Cerdá, C.; Ugarte, M.; Desviat, L.R.
<x xml:space="preserve">Abstract</x> Hereditary tyrosinemia type I (HT1) is a rare disease caused by a deficiency of fumarylacetoacetate hydrolase (FAH) in the tyrosine catabolic pathway, resulting mainly in hepatic alterations due to accumulation of the toxic metabolites fumarylacetoacetate, maleylacetoacetate and succinylacetone. We have characterized using minigenes four splicing mutations affecting exonic or intronic nucleotides of the FAH gene identified in two HT1 patients. Two of the mutations are novel, c.82‐1G>A and c.913G>C and the other two have been previously associated with a splicing defect (c.836A>G and c.1062+5G>A). All mutations were confirmed to affect splicing in minigenes, resulting in exon skipping or activation of a cryptic splice site. We have analyzed the effect of different compounds known to modulate splicing (valproic acid, phenyl butyrate, M344, EIPA, and resveratrol) and the overexpression of splice factors of the SR protein family on the transcriptional profile of the mutant minigenes. For the c.836A>G mutation, a partial recovery of the correctly spliced transcript was observed. These results confirm the relevance of performing functional studies for mutations potentially affecting the splicing process and open the possibility of supplementary therapeutic approaches to diseases caused by splicing defects.